ATTITUDE AND OBSTACLES OF SOCIAL SCIENCE EDUCATION STUDENTS IN PEKANBARU CITY IN FOLLOWING ONLINE LEARNING - Primahardani, Indra; Isjoni, M. Yogi Riyantama (Faculty of Tarbiyah and Teacher Training, Universitas Islam Negeri Alauddin Makassar, 2022)
Online teaching and learning activities can be identified as synchronous and asynchronous learning. This forces every education stakeholder to continue to provide innovation in reducing the impact of learning loss during the COVID-19 pandemic. The research was designed in quantitative descriptive using questionnaire and described in the tables and diagrams forms of survey research method. The population was all students of Social Studies Education of Riau University, Sultan Syarif Kasim State Islamic University, and Riau Islamic University. The research sample was chosen by using a Stratified Random Sampling Technique approach, with 15% of the active students. It was shown that the average score of Social Studies Education students on the three attitude indicators was in the response > 50%, indicating that the attitude of Social Studies Education students participating in online learning in Pekanbaru city was quite good even though there were still obstacles in the learning process. Abstrak: Kegiatan belajar mengajar secara online dapat diidentifikasi sebagai pembelajaran sinkron dan asinkron. Hal ini memaksa setiap stakeholder Pendidikan terus memberikan inovasi dalam mengurangi dampak learning loss selama pandemi COVID-19. Desain penelitian berbentuk kuantitatif guna memberikan jawaban terhadap maksud penelitian dan dijabarkan secara deskriptif dalam bentuk tabel dan diagram. Metode penelitian yang dilakukan yakni dalam bentuk. Tanggapan terhadap angket diidentifikasi sesuai 4 tingkatan Skala Likert. Populasi adalah seluruh mahasiswa Pendidikan IPS di Universitas Riau, Universitas Islam Negeri Sultan Syarif Kasim, dan Universitas Islam Riau. Penyampelan dilakukan melalui pendekatan Stratified Random Sampling Technique, di mana dipilih sebanyak 15% dari mahasiswa aktif semester genap. Secara keseluruhan skor rata-rata mahasiswa Pendidikan IPS terhadap tiga indikator sikap yakni berada pada respon >50%, maka sikap mahasiswa Pendidikan IPS di Kota Pekanbaru selama mengikuti pembelajaran online tergolong baik walaupun masih ditemui hambatan baik dalam bentuk keterbatasan jaringan internet maupun kesulitan memahami materi dalam proses pembelajaran.